Chemical regeneration PA6 / modified nanocellulose composite pipe and preparation method thereof
Patent Information
- Application Number
- CN202611431048.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
原生PA6管材尚且面临长期热氧老化、热水老化等挑战,而再生PA6因杂质和端基结构缺陷,其长期老化性能更加难以保障
[0030] (1) This invention uses a metal ion passivator containing hydrazide groups and/or phosphite groups to effectively complex the residual metal catalyst in chemically regenerated PA6, thereby fundamentally inhibiting the thermo-oxidative degradation reaction catalyzed by metal ions. This enables the long-term wet and hot aging life of regenerated PA6 pipes to reach the level of virgin PA6 pipes, greatly expanding the application of chemically regenerated PA6 in the field of high-end pipes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, specifically to a chemically regenerated PA6 / modified nanocellulose composite pipe and its preparation method. Background Technology
[0002] Polyamide 6 (PA6, commonly known as Nylon 6) is widely used in the manufacture of various pipes, profiles, and engineering plastic products due to its excellent mechanical properties, abrasion resistance, chemical resistance, and processing performance. With the increasing consumption of polyamide materials year by year, the recycling and reuse of waste PA6 products has become an important issue for resource conservation and environmental protection. Chemical depolymerization and repolymerization (i.e., chemical regeneration) is one of the mainstream technical routes for PA6 recycling. This involves depolymerizing waste PA6 products into caprolactam monomers, which are then purified and repolymerized to obtain recycled PA6 resin. However, compared with virgin PA6 resin, chemically recycled PA6 has the following significant drawbacks:
[0003] Firstly, chemically recycled PA6 inevitably contains trace amounts of metal catalysts (such as titanium-based, antimony-based, and tin-based catalysts) used in the depolymerization-repolymerization process. These residual metal ions, especially under humid or high-temperature environments, will catalyze the oxidative degradation of the PA6 molecular chains during long-term use of the pipes, leading to a sharp decline in the material's mechanical properties, yellowing, and embrittlement, severely shortening the service life of the pipes.
[0004] Secondly, during repeated thermal and chemical treatments, recycled PA6 undergoes partial chain breakage, resulting in a significant increase in the content of terminal carboxyl groups (typically 50–130 mmol / kg) and a relative decrease in the content of terminal amino groups (35–85 mmol / kg). This change in end-group structure makes the chemical reactivity and processing stability of recycled PA6 weaker than that of virgin resin. Simultaneously, the molecular weight distribution of recycled PA6 widens, and its melt viscosity fluctuates greatly, posing challenges to the subsequent preparation of composite materials.
[0005] Thirdly, cellulose nanocrystals (CNCs), as a widely available, renewable, biodegradable biomass nano-reinforcing filler with high specific strength and specific modulus, have been attempted for the reinforcement and modification of thermoplastics. However, the surface of cellulose nanocrystals contains a large number of hydrophilic hydroxyl groups, resulting in poor interfacial compatibility with the hydrophobic PA6 matrix. Direct blending leads to agglomeration, hindering the effective exertion of its nano-reinforcing effect. While existing technologies have used silane coupling agents to modify cellulose nanocrystals for enhancing PA6 properties (e.g., Chinese patent application CN118271711A discloses a nanocomposite nucleating agent and a PA6 composite material including it), these primarily focus on virgin PA6 systems and do not consider the impact of changes in the end-group structure of recycled PA6 on interfacial bonding.
[0006] Fourth, pipe products have extremely high requirements for the long-term durability of materials, especially in applications such as water and gas transmission, where pipes need to maintain a long service life in humid and hot environments. Even virgin PA6 pipes face challenges such as long-term thermo-oxidative aging and hot water aging, while recycled PA6, due to impurities and end-group structural defects, has even more difficulty in guaranteeing its long-term aging performance.
[0007] In summary, how to utilize chemically recycled PA6 to produce high-quality pipes with excellent mechanical properties and satisfactory long-term damp heat aging performance is a technical challenge that urgently needs to be addressed in the recycling and reuse of polymer materials. Summary of the Invention
[0008] To address the aforementioned problems, this invention provides a chemically regenerated PA6 / modified nanocellulose composite pipe and its preparation method.
[0009] The technical solution of the present invention is as follows: The present invention provides a chemically recycled PA6 / modified nanocellulose composite pipe, which comprises the following raw materials by weight: 100 parts of chemically recycled PA6 resin, 5-25 parts of modified nanocellulose whiskers, 0.05-3 parts of metal ion passivating agent, 0.1-1.5 parts of heat stabilizer and 0.1-2 parts of lubricant.
[0010] Wherein: the modified nanocellulose whiskers are nanocellulose whiskers surface-treated with a silane coupling agent, and the amount of the silane coupling agent is 5% to 35% of the mass of the nanocellulose whiskers; the metal ion passivating agent contains hydrazide groups and / or phosphite groups, which are used to complex the residual metal ion catalyst impurities in the chemically regenerated PA6 resin; moreover, in the composite pipe, the active groups on the surface of the modified nanocellulose whiskers form hydrogen bonds and / or chemical bonds (the chemical bonds are amide bonds and / or ester bonds) with the terminal carboxyl groups and / or terminal amino groups of the chemically regenerated PA6 resin, and a bonding layer is formed at the interface.
[0011] Preferably, the metal ion passivating agent in the above technical solution is at least one of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine (i.e., MD-1024), bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite (i.e., P-EPQ), and tris[2,4-di-tert-butylphenyl]phosphite (i.e., antioxidant 168).
[0012] More preferably, the metal ion passivating agent is a mixture of MD-1024 and P-EPQ in a mass ratio of 1:(1-3). MD-1024 contains an acylhydrazine group, which has excellent metal ion complexing ability and hindered phenol antioxidant function; P-EPQ contains a phosphite group, which has both metal ion complexing and peroxide decomposition effects, and also has good hydrolytic stability. When the two are mixed in a specific ratio, they can exert a synergistic complexing effect, which is effective against different types and valence states of metal ions (such as Ti). 4+ Sb 3+ Al 3+ All of them (etc.) have excellent complexing and passivation capabilities, and the thermal stability and processing stability of the compound system are better than those of the single component.
[0013] As a preferred technical solution, the silane coupling agent is a silane coupling agent containing amino, epoxy, or methacryloyloxy groups, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (i.e., KH550), γ-glycidoxypropyltrimethoxysilane (i.e., KH560), or γ-methacryloyloxypropyltrimethoxysilane (i.e., KH570).
[0014] More preferably, the silane coupling agent is KH560. The epoxy groups of KH560 can not only react with the hydroxyl groups on the surface of nanocellulose to form strong chemical bonds, but also undergo ring-opening reactions with the terminal carboxyl and terminal amino groups of PA6 during melt blending to form a chemically bonded interface layer with the highest interfacial bonding strength.
[0015] As a preferred technical solution, the cellulose nanofibers have a diameter of 5–20 nm, an aspect ratio of 15–50, and a crystallinity ≥75%. Cellulose nanofibers within this size range possess both high specific surface area and high aspect ratio, which is beneficial for forming a nano-network structure while ensuring its uniform dispersion in the matrix. The chemically regenerated PA6 resin has a relative viscosity of 2.4–3.2 (96% sulfuric acid method), a terminal amino group content of 35–85 mmol / kg, and a terminal carboxyl group content of 50–130 mmol / kg. These end-group content ranges are typical characteristics of chemically regenerated PA6 and are the key material basis for achieving interfacial bonding in this invention.
[0016] As a preferred technical solution, the heat stabilizer is a hindered phenolic antioxidant and / or a phosphite antioxidant; the lubricant is at least one of calcium stearate, zinc stearate, or ethylene bis-stearamide. Hindered phenolic antioxidants (such as antioxidant 1098 and antioxidant 1010) can capture free radicals and interrupt oxidation chain reactions, while phosphite antioxidants can decompose hydrogen peroxides. Together with the metal ion passivator, they constitute a multi-layered stabilization system.
[0017] The chemically regenerated PA6 / modified nanocellulose composite pipe provided by this invention exhibits excellent performance: ring stiffness ≥12 kN / m² (tested according to ISO 9969:2016 standard), and notched impact strength of simply supported beam ≥18 kJ / m² (tested according to ISO 179-1:2023 standard); furthermore, according to ISO 527-1:2012 and ISO 527-2:2025 standards, after aging for 1000 hours under humid heat aging conditions at 70℃ and 95% relative humidity, its tensile strength retention rate is ≥88%, and its elongation at break retention rate is ≥80%. The reasons for achieving these technical effects are mainly due to the following aspects:
[0018] (1) The technical solution provided by this invention can comprehensively form a triple synergistic mechanism of "impurity passivation - interface bonding - nano-reinforcement". Among them, the introduction of metal ion passivating agents into the chemically regenerated PA6 / nanocellulose composite material system can, on the one hand, allow the metal ion passivating agents containing hydrazine groups and / or phosphite groups to react with the residual metal ion catalysts (such as Ti) in the chemically regenerated PA6. 4+ Sb 3+ Sn 2+ (etc.) form stable complexes, effectively inhibiting the catalytic oxidation degradation of PA6 molecular chains by metal ions, fundamentally solving the technical problem of the sensitivity of regenerated PA6 to impurities. On the other hand, the hydrazide group can also react with the terminal carboxyl group of PA6 molecular chain, playing a role in chain extension or end-capping, which helps to improve the molecular weight and melt strength of regenerated PA6.
[0019] (2) This invention transforms the "disadvantage" of the regenerated PA6 end-group structure into the "advantage" of interface enhancement, achieving chemical compatibility between the regenerated PA6 end-group structure and the nanocellulose interface. The nanocellulose whiskers modified with silane coupling agents have active groups (such as amino, epoxy, methacryloyloxy, etc.) on their surface. These active groups can form hydrogen bonds and / or chemical bonds (such as amidation, esterification, etc.) with the terminal carboxyl groups and / or terminal amino groups of the regenerated PA6, constructing a tightly bonded interface layer inside the pipe. This interface layer can not only effectively transfer loads and improve the mechanical properties of the composite material, but also hinder the penetration channels of moisture and oxygen, further improving long-term aging performance.
[0020] (3) Through the nano-reinforcement effect of modified nanocellulose whiskers, the impurity stabilization effect of metal ion passivators and the synergistic effect of interface bonding layer, the ring stiffness and notched impact strength of the composite pipe are significantly improved, greatly enhancing the mechanical properties and long-term resistance to damp heat aging of recycled PA6 pipe, and realizing the high-value recycling of waste PA6 materials.
[0021] This invention also provides a method for preparing chemically regenerated PA6 / modified nanocellulose composite pipes, comprising the following steps:
[0022] (1) Preparation of modified nanocellulose whiskers: Nanocellulose whiskers were dispersed in an alcohol-water mixed solvent, the pH was adjusted to 3.0–5.5, the silane coupling agent was added, and the mixture was stirred and hydrolyzed at 50–80°C for 2–8 hours. After centrifugation, washing, and vacuum drying, the modified nanocellulose whiskers were obtained. In step (1), the pH was controlled at a weakly acidic condition of 3.0–5.5, which is conducive to the hydrolysis and condensation reaction of the silane coupling agent, so that a uniform siloxane coating layer is formed on the surface of the nanocellulose. Too high a temperature or too long a reaction time may cause the coupling agent to self-condense and form free particles, while too low a temperature will result in insufficient hydrolysis.
[0023] (2) Masterbatch pre-dispersion: Take 10% to 30% of the total weight of chemically regenerated PA6 resin and premix it with the modified nanocellulose whiskers obtained in step (1). Then, melt extrusion granulation is performed by a twin-screw extruder to obtain nanocellulose reinforced masterbatch. Since nanocellulose whiskers have a large specific surface area and high surface energy, they are very easy to agglomerate when directly mixed with a large amount of PA6. In this step (2), the "masterbatch method" is used to achieve the pre-dispersion of nanocellulose in the PA6 matrix. That is, the modified nanocellulose whiskers are premixed with a small amount of PA6 resin (10% to 30%) and melt extruded granulation is performed so that the nanocellulose undergoes strong shearing in the high-concentration PA6 melt to achieve preliminary uniform dispersion. When the masterbatch is mixed with the remaining PA6 resin in the subsequent step (3), the nanocellulose can be uniformly distributed in the matrix at the nanoscale, which solves the technical pain point of difficult dispersion of nanofillers.
[0024] (3) Reactive melt blending: The remaining chemically regenerated PA6 resin, the nanocellulose reinforced masterbatch obtained in step (2), the metal ion passivator, the heat stabilizer, and the lubricant are mixed uniformly at high speed and fed into a twin-screw extruder. Melt blending extrusion and granulation are carried out at a melting temperature of 220-260°C and a screw speed of 150-400 rpm to obtain composite granules. During the melt blending process in step (3), several physicochemical changes occur simultaneously: the complexation reaction between the metal ion passivator and the residual metal ions, the chemical bonding reaction between the modified nanocellulose surface active groups and the terminal carboxyl / terminal amino groups of PA6, and the shear dispersion and orientation of nanocellulose. The above reactions are carried out simultaneously under the high temperature and high shear conditions of the twin-screw extruder, and promote each other. After the metal ions are passivated, the thermal degradation of the PA6 molecular chain is inhibited, preventing further disordered changes in the end groups and facilitating the uniformity of the interfacial bonding reaction. The interfacial bonding reaction, in turn, increases the viscosity and strength of the melt, promotes the effective transmission of shear force, and further improves the dispersion of nanocellulose. This "reaction-dispersion-enhancement" linkage mechanism is key to the superior performance of this invention.
[0025] (4) Pipe forming: The composite granules obtained in step (3) are melted and extruded through a pipe extruder, and then vacuum sizing, cooling, and traction cutting are performed to prepare recycled PA6 / modified nanocellulose composite pipe products.
[0026] As a preferred technical solution, in step (1): the alcohol-water mixed solvent is a mixture of anhydrous ethanol and deionized water, with a volume ratio of (1:1) to (4:1); the temperature of the stirring hydrolysis reaction is 60 to 70°C, and the time is 3 to 5 hours. The volume ratio of ethanol to water needs to ensure both the full dissolution and hydrolysis of the silane coupling agent (requiring a certain amount of water) and the good dispersion of nanocellulose in the solvent (ethanol helps to improve wettability). A ratio of 1:1 to 4:1 is the optimal equilibrium range.
[0027] As a preferred technical solution, in step (2): the temperature of each zone of the twin-screw extruder for pre-dispersing the masterbatch is 210-240℃, and the screw speed is 200-300 rpm; in step (3), the temperature of the reactive melt blending is 235-250℃, the screw speed is 250-350 rpm, and the length-to-diameter ratio of the twin-screw extruder is (36:1)-(48:1). A twin-screw extruder with a length-to-diameter ratio greater than 36:1 can provide sufficient residence time and mixing effect, ensuring sufficient dispersion of nanocellulose and effective interfacial reaction.
[0028] As a preferred technical solution, in step (4): the die head temperature of the pipe extruder is 230-250℃, and the ratio of traction speed to extrusion speed is 1.0-1.2. An appropriate traction ratio (stretch ratio) can promote the further orientation of nanocellulose in the pipe along the extrusion direction, improve the circumferential strength and axial strength of the pipe, and at the same time facilitate the further bonding of the interface layer.
[0029] Compared with the prior art, the preparation method of the present invention has the following beneficial effects:
[0030] (1) This invention uses a metal ion passivator containing hydrazide groups and / or phosphite groups to effectively complex the residual metal catalyst in chemically regenerated PA6, thereby fundamentally inhibiting the thermo-oxidative degradation reaction catalyzed by metal ions. This enables the long-term wet and hot aging life of regenerated PA6 pipes to reach the level of virgin PA6 pipes, greatly expanding the application of chemically regenerated PA6 in the field of high-end pipes.
[0031] (2) This invention utilizes the high end carboxyl content of chemically regenerated PA6 as the active site for interfacial chemical bonding, and combines it with nanocellulose whiskers modified by a specific silane coupling agent to construct an interfacial layer with hydrogen bonds and / or chemical bonds in the tube, thereby achieving a strong bond between the regenerated PA6 matrix and the nanocellulose reinforcing phase.
[0032] (3) The metal ion passivating agent and nanocellulose surface modification of the present invention produce a synergistic effect through the chain mechanism of “inhibiting degradation-retaining end groups-promoting bonding-enhancing interface”, so that the composite pipe can still maintain a tensile strength retention rate of more than 88% after 1000h of wet heat aging, which is far greater than the effect achieved by simply superimposing the components.
[0033] (4) The nanocellulose used in this invention is derived from renewable biomass resources, with a wide range of raw material sources and environmental friendliness. The entire preparation process is simple, and the process route can be directly implemented using existing plastic processing equipment without large-scale equipment modification. It has good prospects for industrial promotion and is applicable to multiple fields such as municipal water supply and drainage, chemical liquid transportation, and cable protection. Detailed Implementation
[0034] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment 1 provides a chemically recycled PA6 / modified nanocellulose composite pipe, which is prepared from the following raw materials by weight: 100 parts of chemically recycled PA6 resin (relative viscosity 2.8, terminal amino content 52 mmol / kg, terminal carboxyl content 85 mmol / kg), 15 parts of modified nanocellulose whiskers, 0.5 parts of metal ion passivating agent (MD-1024 and P-EPQ compounded at a mass ratio of 1:2), 0.5 parts of heat stabilizer (antioxidant 1098), and 0.5 parts of lubricant (calcium stearate). The modified nanocellulose whiskers are obtained by surface treatment of nanocellulose whiskers (diameter 5-15 nm, aspect ratio 30:1, crystallinity 82%) with KH560 silane coupling agent, the amount of KH560 being 20% of the mass of the nanocellulose whiskers.
[0037] The preparation method includes the following steps:
[0038] (1) Preparation of modified nanocellulose whiskers: Nanocellulose whiskers were dispersed in a mixed solvent of anhydrous ethanol and deionized water in a volume ratio of 3:1. The pH value was adjusted to 4.5 with glacial acetic acid. KH560 silane coupling agent (20% of the mass of nanocellulose whiskers) was added. The mixture was stirred and hydrolyzed at 65°C for 4 hours. After centrifugation and washing, the mixture was vacuum dried at 60°C for 24 hours to obtain modified nanocellulose whiskers.
[0039] (2) Masterbatch pre-dispersion: Take 20% of the total weight of chemically regenerated PA6 resin and premix it with the modified nanocellulose whiskers obtained in step (1) in a high-speed mixer for 15 minutes. Then put it into a twin-screw extruder for melt extrusion granulation. The temperatures of each zone of the twin-screw extruder are 210℃, 220℃, 230℃, 235℃, 235℃, and 230℃, and the screw speed is 250 rpm to obtain nanocellulose reinforced masterbatch.
[0040] (3) Reactive melt blending: The remaining chemically regenerated PA6 resin (80 parts), the nanocellulose reinforced masterbatch obtained in step (2), MD-1024 / P-EPQ compound passivating agent (0.5 parts), antioxidant 1098 (0.5 parts) and calcium stearate (0.5 parts) are put into a high-speed mixer and mixed evenly. Then, the mixture is put into a twin-screw extruder with a length-to-diameter ratio of 44:1 and temperatures of each zone of 220℃, 235℃, 245℃, 250℃, 250℃, and 245℃. The screw speed is 300 rpm. The mixture is then melt-blended, extruded, and granulated to obtain composite granules.
[0041] (4) Pipe forming: The composite granules obtained in step (3) are melt-extruded through a pipe extruder. The extruder head temperature is 240℃. After vacuum sizing and cooling, the pipe is traction-cut at a ratio of traction speed to extrusion speed of 1.1 to obtain chemically regenerated PA6 / modified nanocellulose composite pipe with an outer diameter of 32mm and a wall thickness of 3mm.
[0042] Example 2
[0043] The difference between Example 2 and Example 1 is that the amount of modified nanocellulose whiskers is 5 parts; the metal ion passivating agent is MD-1024 used alone, with an amount of 0.3 parts; and the silane coupling agent is KH550. The composition of the remaining raw materials and the preparation method are the same as in Example 1.
[0044] Example 3
[0045] The difference between Example 3 and Example 1 is that: the amount of modified nanocellulose whiskers is 25 parts; the metal ion passivating agent is MD-1024 and P-EPQ compounded at a mass ratio of 1:3, and the amount is 2.0 parts; the silane coupling agent is KH570. The composition of other raw materials and the preparation method are the same as in Example 1.
[0046] Example 4
[0047] The difference between Example 4 and Example 1 is as follows: the metal ion passivating agent is antioxidant 168, with a dosage of 1.0 part; the silane coupling agent is KH560; the heat stabilizer is a mixture of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio, with a total dosage of 1.0 part; and the lubricant is ethylene bis-stearamide, with a dosage of 1.0 part. The composition of the remaining raw materials and the preparation method are the same as in Example 1.
[0048] Example 5
[0049] The difference between Example 5 and Example 1 is that in step (1), the volume ratio of anhydrous ethanol to deionized water in the alcohol-water mixed solvent is 2:1, the pH value is adjusted to 3.5, the hydrolysis reaction temperature is 70℃, and the time is 3h. The remaining steps and parameters are the same as in Example 1.
[0050] Example 6
[0051] The difference between Example 6 and Example 1 is that in step (2), the proportion of chemically recycled PA6 resin used for masterbatch pre-dispersion is 10% of the total weight of PA6; in step (3), the melting temperature of the twin-screw extruder is 235-245℃, the screw speed is 250rpm, and the length-to-diameter ratio is 36:1. The remaining steps and parameters are the same as in Example 1.
[0052] Example 7
[0053] The difference between Example 7 and Example 1 is that the lubricant is zinc stearate, and the amount used is 0.5 parts. The composition of the remaining raw materials and the preparation method are the same as in Example 1.
[0054] Example 8
[0055] The difference between Example 8 and Example 1 is that in step (1), the amount of KH560 silane coupling agent is 5% of the mass of nanocellulose whiskers; the composition of the remaining raw materials and the preparation method are the same as in Example 1.
[0056] Example 9
[0057] The difference between Example 9 and Example 1 is that in step (1), the amount of KH560 silane coupling agent is 35% of the mass of nanocellulose whiskers; the composition of other raw materials and preparation methods are the same as in Example 1.
[0058] Comparative Example 1 (without metal ion passivating agent)
[0059] The difference between Comparative Example 1 and Example 1 is that no metal ion passivating agent is added, while the composition of other raw materials and preparation methods are the same as in Example 1.
[0060] Comparative Example 2 (without nanocellulose reinforcement)
[0061] The difference between Comparative Example 2 and Example 1 is that no modified nanocellulose whiskers are added (i.e., the amount of nanocellulose is 0 parts), and the masterbatch pre-dispersion operation in step (2) is omitted accordingly. In step (3), all chemically regenerated PA6 resin is directly mixed with metal ion passivating agent, heat stabilizer and lubricant. The rest is the same as in Example 1.
[0062] Comparative Example 3 (unmodified nanocellulose)
[0063] The difference between Comparative Example 3 and Example 1 is that the nanocellulose whiskers were not surface-modified with a silane coupling agent, and step (1) omitted the silane coupling agent modification treatment. Unmodified nanocellulose whiskers were directly used for masterbatch pre-dispersion. The composition of other raw materials and preparation methods are the same as in Example 1.
[0064] Comparative Example 4 (The metal ion passivator is a non-complexing antioxidant)
[0065] The difference between Comparative Example 4 and Example 1 is that the metal ion passivator is replaced with an equal amount (0.5 parts) of a common hindered phenolic antioxidant (antioxidant 1076), which does not contain hydrazide groups or phosphite groups and does not have the ability to complex metal ions. Everything else is the same as in Example 1.
[0066] Performance testing and characterization
[0067] The composite pipes prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to the following performance tests, and the test results are summarized in Table 1.
[0068] (1) Ring stiffness: Tested according to ISO 9969:2016 standard. The length of the pipe sample is 300mm. A compression test is carried out on a universal testing machine to calculate the ring stiffness value.
[0069] (2) Notched impact strength of simply supported beam: Tested according to ISO 179-1:2023 standard. The specimen is a standard impact specimen cut from the pipe with a type A notch and a pendulum energy of 1J.
[0070] (3) Damp heat aging test: According to ISO 527-1:2012 and ISO 527-2:2025 standards, the pipe is cut into dumbbell-shaped tensile specimens and placed in a constant temperature and humidity chamber. After aging for 1000 hours at a temperature of 70℃ and a relative humidity of 95%, the specimens are taken out and the tensile strength and elongation at break after aging are tested, and the retention rate is calculated. Tensile strength retention rate (%) = (tensile strength after aging / tensile strength before aging) × 100%; the elongation at break retention rate (%) is calculated similarly.
[0071] Table 1: Performance test results of Examples 1-9 and Comparative Examples 1-4
[0072]
[0073] As can be seen from the comparison of test results in Table 1, the overall performance of all embodiments of the present invention is superior to that of the comparative examples, fully demonstrating the effectiveness of the synergistic mechanism of "impurity passivation-interfacial bonding-nano-enhancement", which is specifically reflected in the following aspects:
[0074] (1) All embodiments meet the performance target requirements. The ring stiffness of embodiments 1 to 9 is ≥12.8kN / m², the impact strength is ≥18.8kJ / m², the tensile strength retention rate after 1000h of damp heat aging is ≥89.6%, and the elongation at break retention rate is ≥82.5%.
[0075] (2) The metal ion passivator plays a decisive role in long-term aging performance. Comparative Example 1, without the addition of a metal ion passivator, has initial mechanical properties similar to Example 1 (ring stiffness of 13.2 kN / m² lower than Example 1's 15.6 kN / m², impact strength of 18.7 kJ / m² lower than Example 1's 22.4 kJ / m²), but the retention rate of tensile strength (68.5%) and elongation at break (55.3%) after aging are much lower than Example 1 (92.3% and 85.7%, respectively), by 23.8 and 30.4 percentage points, respectively. This proves that without a passivator to complex and regenerate the residual metal ions in PA6, the material will undergo severe catalytic degradation in a humid and hot environment, and its long-term performance cannot be guaranteed.
[0076] (3) Nanocellulose is the core reinforcing phase for mechanical properties. Comparative Example 2, which did not contain any nanocellulose, had a ring stiffness (8.5 kN / m²) and impact strength (12.3 kJ / m²) that were much lower than those of Example 1, with reductions of 45.6% and 45.1%, respectively. This indicates that nanocellulose is indispensable for improving the rigidity and toughness of the pipe.
[0077] (4) Silane coupling agent modification is a prerequisite for achieving effective reinforcement. Comparative Example 3 uses unmodified nanocellulose, and its ring stiffness (10.8 kN / m²), impact strength (15.1 kJ / m²), and tensile strength retention rate after aging (75.8%) are significantly lower than those of Example 1. This indicates that the unmodified nanocellulose has a weak interface with the PA6 matrix, cannot effectively transfer load, and the interface defects accelerate the aging process.
[0078] (5) The function of the metal ion passivator is specific. Comparative Example 4 uses a common hindered phenolic antioxidant instead of the metal ion passivator containing hydrazide / phosphite groups of the present invention. Its tensile strength retention rate (72.1%) and elongation at break retention rate (58.7%) after aging are much lower than those of Example 1. This shows that although the common antioxidant can capture free radicals, it cannot complex metal ions. Therefore, it cannot fundamentally inhibit the degradation reaction catalyzed by metal ions. Its mechanism of action is fundamentally different from that of the passivator of the present invention.
[0079] (6) Effect of silane coupling agent dosage. As can be seen from the comparison of Examples 1, 8 and 9, when the dosage of coupling agent is 5% of the mass of nanocellulose whiskers (Example 8), the degree of interface modification is low, and although the overall performance meets the standard, it is lower than that of Example 1; when the dosage of coupling agent is increased to 35% (Example 9), the performance is significantly improved compared with Example 8 and close to that of Example 1, indicating that effective interfacial bonding can be achieved in the range of 5% to 35%, of which about 20% is the better implementation range.
[0080] (7) Applicability of Lubricant Type. Example 7 uses zinc stearate as a lubricant, and its overall performance is basically the same as that of Example 1 (calcium stearate), which specifically illustrates that the lubricant type defined in this invention can be well applied to this system.
[0081] Comprehensive comparison reveals that: the lack of a metal ion passivator (Comparative Example 1) leads to severe deterioration of aging performance; the lack of nanocellulose (Comparative Example 2) results in severely insufficient mechanical properties; unmodified nanocellulose (Comparative Example 3) leads to a significant decrease in both reinforcing effect and aging performance; and an inappropriate type of passivator (Comparative Example 4) fails to achieve the metal ion complexation function. Any of the above deficiencies prevents the achievement of the comprehensive performance target of this invention, demonstrating that this invention achieves a synergistic effect of "impurity passivation - interfacial bonding - nano-reinforcement." Under the complete technical solution of this invention, each component sequentially achieves the comprehensive effect of high strength, high toughness, and excellent long-term resistance to damp heat aging, as shown in the examples, through a chain-like synergistic mechanism of "passivator complexing metal ions, inhibiting PA6 molecular chain degradation, retaining end-group active sites, and chemically bonding with modified nanocellulose surface groups, ultimately forming a robust interfacial layer."
[0082] The technical solution, implementation methods, and technical effects of the present invention have been described in detail above. It should be noted that those skilled in the art should understand that the above content is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention. For example, the dosage of each component in the present invention can be adjusted according to actual needs within the range defined in the claims; in addition to KH550, KH560, and KH570, other silane coupling agents containing amino, epoxy, or methacryloyloxy groups can also be selected; in addition to MD-1024, P-EPQ, and antioxidant 168, other compounds containing hydrazide groups or phosphite groups can also be used as metal ion passivating agents; the size and specifications of the pipes can be flexibly adjusted according to actual application needs, all of which can achieve the basic technical effects of the present invention.
Claims
1. A chemically recycled PA6 / modified nanocellulose composite pipe, characterized in that, The raw materials comprised by weight are as follows: 100 parts of chemically regenerated PA6 resin, 5-25 parts of modified nanocellulose whiskers, 0.05-3 parts of metal ion passivating agent, 0.1-1.5 parts of heat stabilizer, and 0.1-2 parts of lubricant; the modified nanocellulose whiskers are nanocellulose whiskers surface-treated with a silane coupling agent, wherein the amount of silane coupling agent used in the treatment process is 5%-35% of the mass of the nanocellulose whiskers; the metal ion passivating agent contains hydrazine groups and / or phosphite groups, used to complex residual metal ion catalyst impurities in the chemically regenerated PA6 resin; In this composite pipe, the active groups on the surface of the modified nanocellulose whiskers form hydrogen bonds and / or chemical bonds with the terminal carboxyl groups and / or terminal amino groups of the chemically regenerated PA6 resin.
2. The chemically recycled PA6 / modified nanocellulose composite pipe according to claim 1, characterized in that: The metal ion passivating agent is at least one of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and tris[2,4-di-tert-butylphenyl]phosphite.
3. The chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 1, characterized in that: The silane coupling agent is a silane coupling agent containing amino, epoxy, or methacryloyloxy groups, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.
4. The chemically recycled PA6 / modified nanocellulose composite pipe according to claim 1, characterized in that: The nanocellulose whiskers have a diameter of 5–20 nm, an aspect ratio of 15–50, and a crystallinity of ≥75%; the chemically regenerated PA6 resin has a relative viscosity of 2.4–3.2, a terminal amino content of 35–85 mmol / kg, and a terminal carboxyl content of 50–130 mmol / kg.
5. The chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 1, characterized in that: The heat stabilizer is a hindered phenolic antioxidant and / or a phosphite antioxidant; the lubricant is at least one of calcium stearate, zinc stearate or ethylene bis-stearamide.
6. A method for preparing the chemically regenerated PA6 / modified nanocellulose composite pipe as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Preparation of modified nanocellulose whiskers: Nanocellulose whiskers are dispersed in an alcohol-water mixed solvent, the pH value is adjusted to 3.0-5.5, the silane coupling agent is added, and the mixture is stirred and hydrolyzed at 50-80℃ for 2-8 hours. After centrifugation, washing and vacuum drying, the modified nanocellulose whiskers are obtained. (2) Masterbatch pre-dispersion: Take 10% to 30% of the total weight of chemically regenerated PA6 resin and premix it with the modified nanocellulose whiskers obtained in step (1). Then, melt extrusion granulation is performed by twin-screw extruder to obtain nanocellulose reinforced masterbatch. (3) Reactive melt blending: The remaining chemically regenerated PA6 resin, the nanocellulose reinforced masterbatch obtained in step (2), the metal ion passivator, the heat stabilizer and the lubricant are mixed evenly at high speed and fed into a twin-screw extruder. The mixture is then melt blended and extruded and granulated at a melting temperature of 220-260°C and a screw speed of 150-400 rpm to obtain composite granules. (4) Pipe forming: The composite granules obtained in step (3) are melted and extruded through a pipe extruder, and then vacuum sizing, cooling, and traction cutting are performed to obtain chemically regenerated PA6 / modified nanocellulose composite pipes.
7. The method for preparing chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 6, characterized in that, In step (1): the alcohol-water mixed solvent is a mixture of anhydrous ethanol and deionized water with a volume ratio of (1:1) to (4:1); the temperature of the stirring hydrolysis reaction is 60 to 70°C and the time is 3 to 5 hours.
8. The method for preparing chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 6, characterized in that, In step (2): the temperature of each zone of the twin-screw extruder is 210-240℃ and the screw speed is 200-300rpm; in step (3): the temperature of the reactive melt blend is 235-250℃, the screw speed is 250-350rpm, and the length-to-diameter ratio of the twin-screw extruder is (36:1)-(48:1).
9. The method for preparing chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 6, characterized in that, In step (4): the die head temperature of the pipe extruder is 230-250℃, and the ratio of traction speed to extrusion speed is 1.0-1.
2.
10. The method for preparing chemically regenerated PA6 / modified nanocellulose composite pipe according to claim 6, characterized in that: The composite pipe has a ring stiffness ≥12 kN / m² and a notched impact strength of a simply supported beam ≥18 kJ / m². After aging for 1000 hours under humid heat aging conditions of 70℃ and 95% relative humidity, its tensile strength retention rate is ≥88% and its elongation at break retention rate is ≥80%.
Citation Information
Patent Citations
Nano composite nucleating agent and PA6 composite material comprising same
CN118271711A